1973
DOI: 10.1104/pp.51.4.702
|View full text |Cite
|
Sign up to set email alerts
|

“Survival” of Mitochondria in Vitro

Abstract: Isolated mitochondria have been maintained active and coupled for 72 hours at 25 C. Survival (retention of respiratory control) is a function of incubation temperature and dependent upon aeration and substrate. ATP does not entirely substitute for substrate, indicating a need for products of active metabolism other than energy. An improvement in respiratory control is often observed during the first several hours of incubation. Sedimentation and resuspension at 24-hour intervals prolonged survival. As revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…ATP will support restoration, metabolically derived energy appears to be more effective. The latter observation is consistent with earlier studies on the requisites for long-term maintenance ofenergylinked functions under energized conditions (32), and in the restoration of state 3 rates reported by Raison et al (27). It is also in accord with Luzikov's (17) contention that various mitochondrial systems are kept functional more by underlying metabolic activity than by available energy per se.…”
Section: Energy Requirementsupporting
confidence: 82%
See 3 more Smart Citations
“…ATP will support restoration, metabolically derived energy appears to be more effective. The latter observation is consistent with earlier studies on the requisites for long-term maintenance ofenergylinked functions under energized conditions (32), and in the restoration of state 3 rates reported by Raison et al (27). It is also in accord with Luzikov's (17) contention that various mitochondrial systems are kept functional more by underlying metabolic activity than by available energy per se.…”
Section: Energy Requirementsupporting
confidence: 82%
“…The latter, which relies largely on the removal ofharmful substances and the use ofprotective agents, has passive connotations. Maintenance, on the other hand, is dynamic and energy-dependent (32). Nonetheless, confirmation of mitochondrial self-restoration calls for direct evidence along the lines first explored in a preliminary study by Romani and Howard (30).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, Romani et al (26) discerned a ripening, age-related change in the mitochondrial system based on the observation that mitochondria in climacteric pears can neither withstand nor recover from doses of ionizing radiation that are tolerated by mitochondria in preclimacteric fruit.It has since been shown that isolated pear and avocado mitochondria can maintain RC' at 25 C for several hr (23,24). In analogy to experiments with long lived chloroplasts (6, 18), the maintenance of RC at 25 C has been referred to (24) as "survival."…”
mentioning
confidence: 99%